Exploring potential mechanistic aspects of “Biaoben acupoint” acupuncture for lumbar disc herniation using 4D proteomics - Shi, Fudong; Wu, Zhiyi; Li, Zuoxu; Jin, Jiao; Lin, Hai; Liu, Ning; Wang, Guojun; Chen, Chun; Feng, Yadi; Liu, Yuzhang; Zhang, Shimin (Frontiers in Neurology, 2025)
ObjectiveTo investigate the mechanism of action of “Biaoben acupoint” acupuncture in treating lumbar disc herniation (LDH) by identifying differentially expressed plasma proteins (DEPs) using timsTOF Pro-based 4D data-independent acquisition (DIA) proteomics and correlating them with clinical indicators.MethodsThis study enrolled 10 healthy individuals (H group) and 10 patients diagnosed with LDH. Plasma samples were collected from LDH patients both before treatment (LDH group) and after three weeks of “Biaoben acupoint” acupuncture treatment (Acu group). Clinical outcomes, including Visual Analogue Scale (VAS) for pain, Oswestry Disability Index (ODI) for lumbar function, and Japanese Orthopaedic Association (JOA) score for neurological status, were assessed before and after treatment. Plasma samples were collected for proteomic analysis and key core proteins were further validated by ELISA.ResultsAcupuncture treatment significantly improved VAS, ODI, and JOA scores in the Acu group compared to the LDH group (p < 0.001). Proteomic analysis quantified 3,685 proteins, identifying 376 DEPs across the healthy group and the experimental group (before and after treatment). Bioinformatics analysis revealed that these DEPs were primarily enriched in pathways related to cell structure and adhesion (e.g., cytoskeleton remodeling, focal adhesion), inflammation and immune signaling (e.g., chemokine and cytokine signaling), and cell signal transduction (e.g., calcium signaling, Rap1 pathway). Core DEPs included ACTB, CXCR4, ACTN1, CXCL12, SELP, and CCN2. Correlation analysis demonstrated that the expression levels of CXCL12, ACTN1, CXCR4, and CCN2 were significantly correlated with VAS, ODI, and JOA scores. To further validate these findings, ELISA was performed on plasma samples from all three groups. The results confirmed that CXCL12, CXCR4, and CCN2 levels were significantly elevated, while ACTN1 was decreased in the LDH group compared to healthy controls; these changes were reversed following acupuncture treatment, showing trends consistent with the proteomic data.Conclusion“Biaoben acupoint” acupuncture likely exerts its therapeutic effects by modulating multiple biological pathways related to inflammatory/immune responses, cytoskeleton organization, cell structure/adhesion, and tissue repair, thereby improving pain, lumbar function, and neurological deficits in LDH patients. Proteins such as CXCL12, ACTN1, CXCR4, and CCN2 are potential key mediators of these therapeutic effects.